Analisis konsumsi kafein sebelum latihan olahraga: Analysis of the caffeine consumption before the training of the sport - Husainiyah, Siti Zainab (Widya Kesehatan, 2024)
This study aims to determine the effect of caffeine consumption before exercise on athlete endurance in the sports of soccer, badminton, and karate. Caffeine can help make the body stronger, help maintain overall body fitness and reduce the risk of injury during sports. In addition, caffeine is also able to improve blood circulation by increasing oxygen diffusion to tissues. The research method used is a descriptive qualitative method with a literature study approach to 3 articles with different sports. From the results of the analysis, it was found that caffeine has an effect on increasing the endurance of athletes during exercise.